A new pyramid-based color image representation for visual localization - Urdiales-García, Amalia Cristina; Domínguez, Miguel; De-Trazegnies-Otero, Carmen Lourdes; Sandoval-Hernández, Francisco (Elsevier, 2010)
This paper presents a new algorithm to extract a color graph from a real image so that it can be efficiently represented in a compact way. The proposal presents two main novelties. First, a new PCA-based color feature vector has been defined. This vector is resistant against illumination changes, noise and microtextures. Second, the image is segmented by means of a fast, hierarchical split and merge algorithm based on a pyramid structure that implicitly provides a color graph. In order to test the suitability of the proposed representation technique, simple localization experiments have been conducted in different real environments.
Image and Vision Computing
Keywords: Procesado de imágenes - Técnicas digitales; Image segmentation; Color segmentation; Principal component analysis; Computer vision; Color graph; Outdoors robot localization